1995
DOI: 10.1111/j.1151-2916.1995.tb08871.x
|View full text |Cite
|
Sign up to set email alerts
|

Processing Strategy for Producing Highly Anisotropic Silicon Nitride

Abstract: Silicon nitride with a preferred orientation of large elongated grains was obtained by tape casting of raw powder slurry seeded with rodlike P-Si,N, particles, followed by a gas pressure sintering under 1 MPa nitrogen pressure. The large elongated grains developed from seeds lay in planes parallel to the casting direction in a two-dimensional distribution. Increased fracture toughness (11.1 MPa-m"*) and bending strength (1100 MPa) were achieved in the direction perpendicular to the grains alignment compared to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
121
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 241 publications
(123 citation statements)
references
References 13 publications
2
121
0
Order By: Relevance
“…Compared with untextured Si 3 N 4 , textured Si 3 N 4 has the capability of reaching a bending strength of up to 1.4 GPa and a fracture toughness of up to 14 MPa m 1/2 in the direction perpendicular to the grain alignment. The grain orientation provides more opportunities for crack deflection and bridging in the crack propagation plane perpendicular to the grain alignment, thereby higher fracture toughness [15,[41][42][43]186]. On the one hand, the high bending strength is due to the more uniform 2-D distribution of larger elongated grains, thereby preventing the formation of large defects such as clusters.…”
Section: Rt Strength and Toughnessmentioning
confidence: 99%
See 3 more Smart Citations
“…Compared with untextured Si 3 N 4 , textured Si 3 N 4 has the capability of reaching a bending strength of up to 1.4 GPa and a fracture toughness of up to 14 MPa m 1/2 in the direction perpendicular to the grain alignment. The grain orientation provides more opportunities for crack deflection and bridging in the crack propagation plane perpendicular to the grain alignment, thereby higher fracture toughness [15,[41][42][43]186]. On the one hand, the high bending strength is due to the more uniform 2-D distribution of larger elongated grains, thereby preventing the formation of large defects such as clusters.…”
Section: Rt Strength and Toughnessmentioning
confidence: 99%
“…The higher toughness allows textured Si 3 N 4 to have higher tolerance to flaws generated during machining, thereby improving the mechanical reliability. Hirao et al [43] developed c-axis aligned Si 3 N 4 that exhibited a Weibull modulus of 46. Moreover, Ohji et al [188] observed a steep R-curve behavior for textured Si 3 N 4 , as shown in figure 27, which is believed to be advantageous for avoiding catastrophic fractures and for increasing the Weibull modulus by narrowing the strength distribution.…”
Section: Rt Strength and Toughnessmentioning
confidence: 99%
See 2 more Smart Citations
“…Ceramics having textured structures can be produced by such processes as templated or seed grain growth, 1,2) hot forging or pressing 3,4) and tape casting. 5) On the other hand, since technologies of superconducting magnets were developed, high magnetic field has become one of the effective ways to get the textured structures by controlling crystal alignment. 6) Recently, a lot of new phenomena and functions of materials have been found in the fields of science and engineering relating to the high magnetic field.…”
Section: Introductionmentioning
confidence: 99%